The Valentine bears - Bunting, Eve, 1928-; Brett, Jan, 1949- (New York : Clarion Books, 1983)
Mrs. Bear plans a surprise Valentine's Day celebration for Mr. Bear despite their usual hibernating habits at that time of year.
3.2
K-3
K-3
School Library Journal
Publisher's Weekly
Booklist
Keywords: Bears -- Fiction; Valentine's Day -- Fiction; Hibernation -- Fiction; Bears -- Fiction; Valentine's Day -- Fiction; Hibernation -- Fiction